2022
DOI: 10.15294/kemas.v18i2.31555
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Improvement by Comprehensive Holistic Services at Public Health Centre X Surabaya

Abstract: Comprehensive holistic health services are a form of improving the quality of health services by measuring IKM. The result of a survey by BPJS Kesehatan is that the IKM has not reached targeted satisfaction in 2016 and 2017. Public Health Center X has an index value that exceeds the existing IKM target, but the index value is lower than the index value in 2016. This study will analyze the decrease in the satisfaction index of BPJS participants towards First-Level Healthcare Facilities (FKTP). Then the low sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are five aspects in measuring service quality (SERVQUAL), namely: reliability, responsiveness, guarantee, empathy and physical evidence (Bayu Yustisia, 2017). According to research by Wartiningsih (2022), the reliability aspect is the ability of health facilities to provide promised services satisfactorily and accurately. study conducted by Meesala & Paul (2018) found that reliability and responsiveness (not empathy, realness, and reassurance) impact patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are five aspects in measuring service quality (SERVQUAL), namely: reliability, responsiveness, guarantee, empathy and physical evidence (Bayu Yustisia, 2017). According to research by Wartiningsih (2022), the reliability aspect is the ability of health facilities to provide promised services satisfactorily and accurately. study conducted by Meesala & Paul (2018) found that reliability and responsiveness (not empathy, realness, and reassurance) impact patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The Iconesia survey institute recorded data on the satisfaction of the people of Surabaya city with health services from community health centers in 2016 that there was a difference between the hope index (79.2%) and the satisfaction index (75.9%). In 2017, Puskesmas X in West Surabaya had a gap in expectations (87.50%) and satisfaction (69.74%) (Wartiningsih, 2022). Based on the explanation and information provided, this research is important because since the elderly polite community health center program was introduced in 2003, there are still very few community health centers that have implemented it.…”
Section: Introductionmentioning
confidence: 99%